PENGARUH DISIPLIN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN (Studi pada PT. Tanjung Selatan Makmur Jaya Kalimantan Selatan) - Herlina Lusiana; Firdaus Firdaus (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2018)
This research aims to: (1) tested the influence of the discipline of work partially on performance of employees; (2) to test the influence of partially working environment on performance of employees; (3) test the influence of the discipline of work and work environment on performance of employees simultaneously.This research was conducted on the PT Tanjung Selatan Makmur Jaya South Kalimantan. There are 71 respondents that have been selected as the sample slovin formula and using the technique of random sampling. Research method using the methods of survey and the type of quantitative research. While the nature of this research including research eksplanatory. Data retrieval method using questionnaires, while data analysis techniques using multiple linear regression and hypothesis testing using IBM SPSS program Version 24.The results showed that the discipline of work (X1) has a partial influence on performance of employees at PT Tanjung Selatan Makmur Jaya South Kalimantan, the working environment (X2) has a partial influence on performance of employees on PT Tanjung Selatan Makmur Jaya South Kalimantan, and discipline work (X1) and the work environment (X2) features simultaneously influence on performance of employees at PT Tanjung Selatan Makmur Jaya South Kalimantan. From the results of the determination coefficient (R2) of 73% change in the performance of the employees of PT Tanjung Selatan Makmur Jaya South Kalimantan affected by variable discipline of work and work environment. While the rest of IE 27% affected other factors. Keywords: discipline work, the work environment, performance.